Stochastic electrochemistry and photoelectrochemistry of colloidal dye-sensitized anatase nanoparticles at a Pt ultramicroelectrode. (21st September 2016) - Barakoti, Krishna K.; Parajuli, Suman; Chhetri, Pushpa; Rana, Ganesh R.; Kazemi, Rezvan; Malkiewich, Ryan; Alpuche-Aviles, Mario A.
Abstract : We report the stochastic interactions between dye sensitized anatase nanoparticles, suspended in a colloid, and a Pt ultramicroelectrode (UME) that result in step-wise behavior in the current vs. time response. The stochastic currents are observed in the dark and under illumination. In the dark, the currents are anodic, consistent with the oxidation of the dye N719 at the Pt surface. The electrochemical behavior of the dye was investigated in MeOH and MeCN with a quasireversible cyclic voltammogram (CV) observed at 1 V s −1 . The anodic currents observed in the dark due to nanoparticles (NPs) at the Pt surface are consistent with the CVs in MeOH and MeCN. Under illumination cathodic steps are observed and assigned to the reduction of the oxidized form of the dye generated after electrons are injected into the TiO2 NPs. The colloidal behavior is a strong function of the history of the colloid with illumination time increasing the size of the agglomerates and with larger agglomerates being less photoelectrochemically active. Agglomerates of ca. 100 nm in diameter are proposed to be photoactive entities with a higher probability of detection that contribute to the staircase photocurrent response.